Developing A Maslahah-Based Model Of Islamic Social Entrepreneurship Through Impact Investment: An Al-Ghazali Perspective - Sifwatir Rif'ah; Muhammad Lathoif Ghozali (JOURNAL OF SHARIA ECONOMICS, 2026)
This study aims to analyze Islamic Social Entrepreneurship (ISE) and impact investment from the perspective of Al-Ghazali’s maslahah and to develop a conceptual model for sustainable economic development. This research employs a qualitative approach using a systematic literature review of Scopus and Sinta-indexed journals from 2020–2025. The findings reveal that ISE and impact investment are inherently aligned with Islamic economic principles, emphasizing a balance between financial returns and social impact. From Al-Ghazali’s perspective, economic activities should be oriented toward maslahah, encompassing justice, social welfare, and public benefit. This study proposes a novel conceptual model integrating Islamic social finance and impact investment within a maslahah-based framework, consisting of input, process, and output components. The model offers a value-based approach to fostering inclusive and sustainable economic development.